Knowledge and Attitude of HIV Counselling and Testing among Males Aged 18-30 Years in Kyeizooba Community, Bushenyi District. - Niwamanya, Blutus (Student’s Journal of Health Research Africa, 2021)
Background: In 2018, an estimated 1.4 million people were living with HIV, and an estimated 23,000 Ugandans died of AIDS-related illnesses. As of 2018, the estimated HIV prevalence among adults (aged 15 to 49) stood at 5.7 %. HIV testing is often used as an umbrella term to refer to both testing and counseling services. The use of HIV testing and counseling is closely related to education level, fear to disclose results, stigma, and discrimination towards HIV/AIDs patients. In the Kyeizooba sub-county, there is a low turn up for HCT services among males aged 18-30 years compared to females of the same age and the reasons behind the cause are missing. Methods: This was a cross-sectional study design that used, convenient sampling to get the needed participants. The sample size was determined by Kish &Lesley (1965) method of sample estimation. All participants that met the inclusion criteria were 78. A self-administered questionnaire was used to collect the data and analyzed using SPSS 20.0. Permission was sought from the nursing department, faculty research committee from MUST, and further permission from DHO. Results: Most participants were married (37.2%), secondary level (44.9%), and unemployed youth (42.3%). Most of the participants scored between 5-7 as moderate knowledge. Most of the participants scored below 22.5 with an average score of 16.6 (negative attitude) others agreed with blood loss during testing, stress, stigma, and discrimination. Most had never tested 68%, preferred health facility48.7% as a testing site. Conclusion: Most of the participants had moderate knowledge which is attributed to education level and most had a negative attitude towards HCT.